Language, Literacy, and Learning in Primary Schools : Implications for Teacher Development Programs in Nigeria - Adekola, Olatunde A. (Washington, DC: World Bank, 2012)
Language, Literacy, and Learning in Primary Schools is a synthesis of the findings arising from four years of policy research and development in Nigeria's primary schools that focused on the gap between what teachers should know and be able to do, and the realities of teaching and learning in classrooms. It begins by critically examining the outcomes of primary schooling as measured by learning achievement results from national assessments, and by identifying some core learning problems for Nigerian primary school children. It reviews the findings from recent research reports that studied teaching and learning processes in primary school classrooms, and it identifies the pedagogical issues in primary classrooms that contribute to poor learning achievements. This report describes a research and development program that set out to improve teaching and learning in core learning skill areas of the curriculum.